The Effect of Human Immunodeficiency Virus Prevention and Reproductive Health Text Messages on Human Immunodeficiency Virus Testing Among Young Women in Rural Kenya: A Pilot Study. Issue 6 (June 2016) - Njuguna, Njambi; Ngure, Kenneth; Mugo, Nelly; Sambu, Carrole; Sianyo, Christopher; Gakuo, Stephen; Irungu, Elizabeth; Baeten, Jared; Heffron, Renee
Abstract : Background: More than half of human immunodeficiency virus (HIV)–infected individuals in Kenya are unaware of their status, and young women carry a disproportionate burden of incident HIV infections. We sought to determine the effect of an SMS intervention on uptake of HIV testing among female Kenyan college students. Methods: We conducted a quasi-experimental study to increase HIV testing among women 18 to 24 years old. Four midlevel training colleges in Central Kenya were allocated to have their study participants receive either weekly SMS on HIV and reproductive health topics or no SMS. Monthly 9-question SMS surveys were sent to all participants for 6 months to collect data on HIV testing, sexual behavior, and HIV risk perception. We used multivariate Cox proportional hazards regression to detect differences in the time to the first HIV test reported by women during the study period. Results: We enrolled 600 women between September 2013 and March 2014 of whom 300 received weekly SMS and monthly surveys and 300 received only monthly surveys. On average, women were 21 years of age (interquartile range, 20–22), 71.50% had ever had sex and 72.62% had never tested for HIV. A total of 356 women reported testing for HIV within the 6 months of follow-up: 67% from the intervention arm and 51% from the control arm (hazard ratio, 1.57; 95% confidence interval, 1.28–1.92). Conclusions: Use of weekly text messages about HIV prevention and reproductive health significantly increased rates of HIV testing among young Kenyan women and would be feasible to implement widely among school populations. Abstract : Young Kenyan women receiving monthly human immunodeficiency virus awareness text messages reported testing for human immunodeficiency virus more frequently than those not receiving any messages.